The Skilled Helper : A Problem-Management Approach to Helping - Egan, Gerard (Pacific Grove, Calif. ; London : Brooks/Cole, 1998)
Internationally recognised for its successful problem-management approach to effective helping, this book offers a step-by-step guide to the counselling process. This new edition includes updated graphics throughout.
Previous ed.: 1995.
Ill. on lining papers.
Includes bibliographical references (p. 345-363) and index.
Keywords: Counseling; Therapist and patient; Society